Myelination as Assessed by Conventional MR Imaging is Normal in Young Children with Idiopathic Developmental Delay - Maricich, S.M.; Azizi, P.; Jones, J.Y.; Morriss, M.C.; Hunter, J.V.; Smith, E.O.; Miller, G. (American Journal of Neuroradiology, 2007)
BACKGROUND AND PURPOSE: A common isolated reported finding in brain imaging studies on developmentally delayed children is delayed myelination. We hypothesized that brain MR imaging scans of these children would show delayed subcortical myelination of white matter with specific involvement of the subcortical U-fibers as these represent terminal zones of myelination and are the last areas to myelinate.MATERIALS AND METHODS: A total of 93 children (31 controls, 62 with idiopathic developmental delay [IDD]) aged 17 to 46 months were identified on the basis of having brain MR imaging for evaluation of IDD (cases) or for another condition (controls). Children with diseases that primarily affect white matter or overt intracranial lesions or malformations were excluded. IDD was defined as psychomotor retardation without a clear cause on the basis of history, physical, genetic, metabolic, and neuroimaging examinations. Developmental quotients (DQs) were calculated for all children with IDD on the basis of clinical history, examination, and psychometric testing. Three board-certified pediatric neuroradiologists examined axial T2-weighted brain images and used a published scoring system to rate the extent of myelination in the frontal, temporal, parietal, and peritrigonal brain regions. In addition, subcortical U-fibers in the frontal, temporal, and parietal lobes were scored separately. Data were analyzed at both the intraobserver and interobserver levels, and scores were compared between groups and tested for interactions with age and DQ.RESULTS: There were no differences in the timing or extent of myelination in the control and IDD groups at any age in any brain region. In the IDD group, there was no relationship between myelination scores and DQ or developmental domain.CONCLUSIONS: Our findings did not support the hypothesis that there is a correlation between IDD and the maturity of myelination, including the terminal zones, as seen on conventional brain MR imaging. Neuroimaging evaluation of maturity of subcortical myelination is not a marker of IDD in young children, and the isolated “finding” of delayed myelination should be interpreted with caution.